The Effect of Viral Marketing and Flash Sale on Impulsive Buying on Wardah Products on The Tiktok Shop Marketplace (Case Study on Students of Management Program, Undikma) - Ajizah Nuramalia,; Menik Aryani,; Ira Dianti, (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
Wardah is a product that is always Viral when releasing the latest product and always provides a Flash Sale during live streaming on the Tiktok Shop application, thus the author conducted a study related to "the effect of Viral Marketing and Flash Sale on Impulsive Buying on Wardah products in the TikTok Shop marketplace. This study was conducted with the aim of finding out the influence of Viral Marketing and Flash Sale on Impulsive Buying on Wardah products in the TikTok Shop marketplace using quantitative research methods. Primary data in this study was obtained from a questionnaire filled out by 113 respondents and then processed using SPSS. The results of the study were obtained from the T test and the F test which was carried out so that it was found that the Viral Marketing and Flash Sale variables had a significant influence partially and simultaneously on impulsive buying. And a determination test (R2) was carried out, the results were obtained that 93.8% of the X variable affected the Y variable and 6.2% were unknown because it was outside the research model. Keywords: Viral Marketing, Flash Sale, Impulsive Buying